PERAN PEMUDA SEBAGAI AGEN OF CHANGE DALAM GEREJA BERDASARKAN MATIUS 5:13-16 - Chlaudea Mangoting; Mitra Gabriella Kombong, Rismayuni Sarah Londong, Minarianti Tandi Ra'ba, Yanti Arrang (ADISAM PUBLISHER, 2024)
This research aims to explore and understand the role of youth as agents of change in the church context, focusing on the teachings of Jesus in Matthew 5:13-16. The study will analyze how youth can become the